2019
DOI: 10.22146/ijc.37513
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Converting Enzyme (ACE) Inhibitory Activity of Peptide Fraction of Germinated Pigeon Pea (<i>Cajanus cajan</i> (L.) Millsp.)

Abstract: During the germination process, seeds can release various types of peptides due to the degradation of storage proteins. Some of these peptides can have biological activity (bioactive peptides). The objective of this study was to determine the ACE inhibitory activity of germinated pigeon pea peptide extract at various germination times and to carry out the fractionation to the extract to get the most active peptide fraction. The results showed that the highest activity of peptide extract was found on the 4th-da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
(13 reference statements)
0
4
0
1
Order By: Relevance
“…Generally, the newly formed peptides would also possess their specific steric and electronic properties and then play important role for the physiological regulatory function (Acquah et al ., 2018). Currently, several reports have focused on the influence of gastrointestinal digestion on food protein‐derived peptides with the antioxidant, angiotensin I‐converting enzyme (ACE‐I) inhibitory as well as anti‐inflammatory capacity (Ratnayani et al ., 2019; Paul, et al ., 2021; Shi et al ., 2021). Most of the biological activity was enhanced during gastrointestinal hydrolysis due to the production of small peptides.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the newly formed peptides would also possess their specific steric and electronic properties and then play important role for the physiological regulatory function (Acquah et al ., 2018). Currently, several reports have focused on the influence of gastrointestinal digestion on food protein‐derived peptides with the antioxidant, angiotensin I‐converting enzyme (ACE‐I) inhibitory as well as anti‐inflammatory capacity (Ratnayani et al ., 2019; Paul, et al ., 2021; Shi et al ., 2021). Most of the biological activity was enhanced during gastrointestinal hydrolysis due to the production of small peptides.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, all the fractions showed good (>50%) inhibitory activity toward ACE (55.2 to 78.6%), although significant ( p < .05) decreases with increase in peptide size was observed. A recent research reported a higher ACE‐inhibitory activity (86.97%) for <3 kDa peptide from 4 days germinated pigeon pea and attributed this activity to the presence of low molecular weight (<1 kDa) peptides with relatively high hydrophobic amino acids (Ratnayani, Suter, Antara, & Putra, 2019a). These findings indicate that the PPHT and peptide fractions possess strong ACE‐inhibitory activity and could be useful as functional ingredients to formulate foods with potential to modulate hypertension.…”
Section: Resultsmentioning
confidence: 99%
“…Oleh karena itu, penggunaan membran UF sangat efisien untuk meningkatkan aktivitas peptida bioaktif (Lassissi et al, 2014). Hal ini didukung oleh penelitian Ratnayani et al (2019) yang mengemukakan bahwa aktivitas ACE inhibitor tertinggi dimiliki olek fraksi terkecil dan Mullally et al (1997) menyatakan bahwa fraksinasi menggunakan membran UF 3 kDa menghasilkan permeat dengan aktivitas ACE inhibitor yang lebih tinggi.…”
Section: Kesimpulanunclassified